2019
DOI: 10.1097/mcg.0000000000001213
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial: Split-dose and Same-day Large Volume Bowel Preparation for Afternoon Colonoscopy Have Similar Quality of Preparation

Abstract: Goals: We compare bowel cleanliness in patients taking same-day versus split-dose 4-L polyethylene glycol laxative for afternoon colonoscopy. Secondary objectives included patient satisfaction, adverse effects and patient tolerability. Background: Afternoon colonoscopies have been associated with inadequate bowel preparation and lower adenoma detection rates. Same-day (morning) or split-dosing of the laxative have improved preparation quality but differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Table 1 summarizes the characteristics of the 18 included studies ( n = 5464), which consisted of 2793 patients who received SSDs and 2671 patients who received the SpDs regimen. Nine trials evaluated low-volume (2 L) SSD PEG with adjuvant laxative use vs large-volume(≥ 3 L) SpDs PEG[ 11 , 12 , 22 - 28 ], four trials compared 4 L SSD PEG vs 4 L SpDs PEG[ 13 , 14 , 19 , 20 ], and six trials compared 2 L SSD PEG vs (≥ 3 L) SpDs PEG[ 11 , 15 - 18 , 21 ]. Interestingly, in a study by Zhang et al [ 11 ], patients were assigned to three groups: 2 L SSD PEG, 2 L SSD PEG with adjuvant laxative (linaclotide) and 4 L SpDs PEG.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 summarizes the characteristics of the 18 included studies ( n = 5464), which consisted of 2793 patients who received SSDs and 2671 patients who received the SpDs regimen. Nine trials evaluated low-volume (2 L) SSD PEG with adjuvant laxative use vs large-volume(≥ 3 L) SpDs PEG[ 11 , 12 , 22 - 28 ], four trials compared 4 L SSD PEG vs 4 L SpDs PEG[ 13 , 14 , 19 , 20 ], and six trials compared 2 L SSD PEG vs (≥ 3 L) SpDs PEG[ 11 , 15 - 18 , 21 ]. Interestingly, in a study by Zhang et al [ 11 ], patients were assigned to three groups: 2 L SSD PEG, 2 L SSD PEG with adjuvant laxative (linaclotide) and 4 L SpDs PEG.…”
Section: Resultsmentioning
confidence: 99%
“…Bowel cleanliness was evaluated either with BBPS[ 11 , 12 , 14 , 15 , 18 , 23 - 27 ] or OBPS[ 13 , 16 , 17 , 19 - 22 , 28 ]. An adequate bowel preparation was defined as a total BBPS score ≥ 6 with all colon segments scores ≥ 2, or a total OBPS score < 5 (including score < 7 by De Leone, score ≤ 3 by Cesaro) or all colon segment OBPS score < 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have showed no substantial differences between split‐dose and same‐day schedules. 39 , 40 , 41 , 42 However, the schedule chosen should be based on the patient's clinical characteristics, including comorbidities, concomitant medications, and hospitalization, and socioeconomic status. 41 , 43 …”
Section: Bp Volumementioning
confidence: 99%
“… 39 , 40 , 41 , 42 However, the schedule chosen should be based on the patient's clinical characteristics, including comorbidities, concomitant medications, and hospitalization, and socioeconomic status. 41 , 43 …”
Section: Bp Volumementioning
confidence: 99%